2021
DOI: 10.3390/ijms22126529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polymer Blending on the Performance of a Subcutaneous Biodegradable Implant for HIV Pre-Exposure Prophylaxis (PrEP)

Abstract: Long-acting (LA) HIV pre-exposure prophylaxis (PrEP) can mitigate challenges of adhering to daily or on-demand regimens of antiretrovirals (ARVs). We are developing a subcutaneous implant comprising polycaprolactone (PCL) for sustained delivery of ARVs for PrEP. Here we use tenofovir alafenamide (TAF) as a model drug. Previously, we demonstrated that the release rates of drugs are controlled by the implant surface area and wall thickness, and the molecular weight (MW) of PCL. Here, we further advance the impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…All implants were fabricated in a biosafety cabinet under aseptic conditions using a previously reported method [ 34 ]. Prior to starting the in vitro studies, all implants were packed within amber glass vials and sterilized using gamma irradiation (dose range 18–24 kGy) at Steris (Mentor, OH, USA) via continuous exposure to a Cobalt-60 gamma-ray source (Nordion Inc., Ottawa, ON, Canada) for 8 h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All implants were fabricated in a biosafety cabinet under aseptic conditions using a previously reported method [ 34 ]. Prior to starting the in vitro studies, all implants were packed within amber glass vials and sterilized using gamma irradiation (dose range 18–24 kGy) at Steris (Mentor, OH, USA) via continuous exposure to a Cobalt-60 gamma-ray source (Nordion Inc., Ottawa, ON, Canada) for 8 h.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the long-acting and sustained co-delivery of ARVs and hormones was shown for multipurpose prevention technology (MPT) indications, where progestins and ARVs were simultaneously delivered for HIV PrEP and contraception [ 32 , 33 ]. These studies showed that the release rate of the drug is controlled by modifying the properties of the polymer tubes such as wall thickness, surface area, PCL molecular weight, and polymer composition (e.g., blends of PCL homopolymers of different molecular weight [ 34 ]). Specifically, PCL tubes with thin walls, large surface areas, and high molecular weights release drugs faster.…”
Section: Introductionmentioning
confidence: 99%
“…We are developing a biodegradable implant for delivery of ARVs for HIV PrEP with promising in vitro and in vivo results previously reported ( Johnson et al, 2019 ; Li et al, 2020 ; Li et al, 2021a ; Li et al, 2021b ). This reservoir-style implant comprises poly (ε-caprolactone) (PCL), which is designed to degrade after multiple years to enable LA delivery of ARVs and could potentially eliminate the need for a medical procedure for implant retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…This reservoir-style implant comprises poly (ε-caprolactone) (PCL), which is designed to degrade after multiple years to enable LA delivery of ARVs and could potentially eliminate the need for a medical procedure for implant retrieval. Previously, we demonstrated our PCL implant provides controlled drug release that is tunable via modifications to the surface area, the thickness of the reservoir-implant wall, and properties of the polymer ( Johnson et al, 2019 ; Li et al, 2021b ). This manuscript describes the developmental path and accompanying preclinical studies of this reservoir-style implant that is designed to release TAF.…”
Section: Introductionmentioning
confidence: 99%